Implementation of Sanctions of Imprisonment in Lieu of a Fine in Illegal Fishing Cases in Indonesia’s Exclusive Economic Zone (ZEEI) - M Marimin (Proceeding International Conference Restructuring and Transforming Law, 2022)
Positive law has emphasized that illegal fishing in ZEEI can only be subject to a fine without being followed by imprisonment in lieu of a fine, but until now there are still practices that deviate from the positive law, such as decision number 71/Pid.Sus-Prk/2017/PN. Ran. This paper will describe the judge’s considerations in the decision and relate it to the doctrine of criminal law for its application in the future. This paper uses doctrinal legal research with a legal, conceptual, and case approach. From the results and discussion, it can be seen that the judge in the decision number 71/Pid.Sus-Prk/2017/PN.Ran who applied the substitute confinement sanction was based on considerations of the value of justice and expediency. Here the judge ignores the value of legal certainty by deviating from the Fisheries Law and SEMA No. 3 of 2015, and the judge was then guided by the Criminal Code. The attitude of the judge who prioritizes justice and expediency needs to be appreciated, but the judge's deviation is not appropriate because in understanding the Fisheries Law, the judge does not pay attention to the UNCLOS 1982 which explicitly states that illegal fishing perpetrators cannot be subject to corporal punishment, including imprisonment. The author suggests that in the future judges rely on progressive legal thinking when they want to apply confinement sanctions in lieu of fines against illegal fishing actors in the ZEEI.